Cohort profile: pulmonary early assessment of the lung in paediatric cancer patients (SWISS-PEARL Study) (Swiss Medical Weekly, 2025)
BACKGROUND: Due to the limited sensitivity of conventional lung function tests in detecting small airway abnormalities, cancer treatment-related pulmonary toxicity may be underdiagnosed. It has been suggested that the nitrogen multiple-breath washout test (N2MBW) might be more sensitive in detecting small airway abnormalities in childhood cancer survivors.OBJECTIVE: The Pulmonary Early Assessment of the Lung in Paediatric Cancer Patients (SWISS-PEARL) study aims to assess the prevalence and development of early pulmonary toxicity at baseline and longitudinally in paediatric cancer patients using spirometry, body plethysmography, diffusing capacity for carbon monoxide (DLCO), N2MBW and magnetic resonance imaging (MRI) and to identify treatment-related pulmotoxic risk factors.METHODS: This prospective, multicentre, cohort study at the University Children’s Hospitals of Basel, Bern, Lausanne and Zurich, is enrolling patients aged ≥4 and